Perancangan Modular Panel Dekoratif Berbahan Dasar Rotan Untuk Interior Bangunan Komersial - Brian Tjiasmanto (Intra, 2017)
The abundance of raw materials such as natural rattan fiber in the country is not necessarily offset by various types of products. During this time, most of rattan processing factories only produce furniture products for residential needs. Gradually, the saturation and decline in rattan production is increasingly felt at local and foreign market. Therefore, product diversification needs to be done to target the wider market. Decorative module-based panels are a great new alternative to increase the absorption of rattan raw materials with more efficient manufacturing systems. Along with the significant growth of commercial buildings, the advantages of rattan-based panels are expected to be applied to various interior elements to enhance the image of related objects and support local nuances in a more modern dressing.